Implementation of 1D–3D integrated model for thermal prediction in internal combustion engines. (25th July 2021) - Margot, X.; Quintero, P.; Gomez-Soriano, J.; Escalona, J.
Abstract: The need to improve the thermal efficiency of gasoline engines used in hybrid vehicles, has led to explore new solutions for reducing engine heat losses. Hence, it is important for the car manufacturers to be able to predict the heat transfer in the engine components. Numerical methods such as CFD (Computational Fluid Dynamics) or CHT (Conjugate Heat Transfer) can be used to assess the heat losses through the combustion chamber walls, but they are long and costly. In this regard, it is particularly interesting for the industry to use simplified models, which may play a key role in the design stage. In this work a 1D model integrated with 3D finite elements based on a commercial software is used to calculate the heat losses in a single-cylinder gasoline direct injection engine. The model is first validated, then a detailed heat transfer analysis is performed, and its results compared to those of a full CFD–CHT simulation. Results demonstrate that this approach is suitable to predict in a short time the heat losses and the spatial temperature distribution in the solid regions of an internal combustion engine. The model also yields accurate values in terms of engine performance. Highlights: 1D–3D fully integrated model to calculate heat transfer in ICE in a few minutes. This method allows calculating solid temperature distribution in a few minutes. Method suitable to estimate spatial temperature distribution in the solid regions. Similar results to experimental data and more precise CHT solutions were found. Temperatures in solid surfaces may be used as boundary conditions for CHT.